O direito ao crédito e a não-cumulatividade do ICMS - Floriano, Daniela Cristina Ismael (2011)
The rule of law that regulates the offsetting credits process constitutionally qualified, which results from the non-cumulative tax principle related to the tax on goods and services (ICMS), is certainly one of the topics most analyzed by Brazilian doctrine. However, the guidance adopted by most researchers and doctrinaires in virtually all the work presented so far was based on identifying the legal nature of the aforementioned offsetting process and on its systematic operation. This paper is based on the approach of another topic on the subject: the presentation of a precise (and necessary) distinction between the concepts of "right to credit" (credit book), and the phenomenology of the offsetting credits process due to the application of procedural rules that govern the non-cumulative system. This paper evidences that there is no necessary connection between those concepts, even though they are closely related. This essay demonstrates that it is possible to identify the credit book without being necessary to assume the supposed standard that guides the offsetting of these credits. In this sense, we conclude that, regardless of whether this is a necessary element for the maintenance of the ICMS in the format in which this tax is governed by the Constitution nowadays (non-cumulative, as a rule), one cannot include the non-cumulative principle in the criteria that compose the matrix rule for levying the ICMS tax. The reason for that is because the legal standard that governs the offsetting engine seeks for fiscal neutrality, and it contains an independent procedural rule itself separated from the charge of the ICMS tax. The distinction between the concepts of credit book and procedural rule is important as we establish the logical-semantic elements that compose the matrix rule of the legal standard for offsetting credits that arise from the non-cumulative system. Identified such criteria, we believe that it will favor the work of the agents that deal with this legal standard